Tourism Awareness Movement through Educreative Program in Dunggala Village, Bone Bolango District - Hari Danial; Sri Agriyanti Mestari; Elsje Louise Sambouw (Yayasan Pendidikan Bima Berilmu, 2022)
Dunggala Village is one of the villages in Tapa District, Bone Bolango Regency which is the center of Miranti bathing tourism and the tomb of King Blongkod. Not to mention, currently the Dunggala Village area is a rafting destination located at Langge Hils Resort. But unfortunately, the lack of public attention, including tourists, government and business actors towards tourism awareness, makes this not work well, including there are still many street vendors who do not pay attention to the cleanliness of their merchandise and place, lack of good interaction in entertaining guests using English. as well as Indonesian. Many of the community components do not pay attention to the importance of tourism awareness as an intervention in community economic development. The MBKM program